Optimizing tilt angle of the roof for the best performance ratio of rooftop photovoltaic - Dani Ali, Nurhalim; Bahri, Syaiful; Ikhwan Siregar, Yusni; Suwondo, Suwondo; Anhar, Anhar; Lysbetti Marpaung, Noveri; Muhammad, Juandi; Hasyim Rosma, Iswadi (Bulletin of Electrical Engineering and Informatics, 2025)
Rooftop photovoltaic (RPV) systems are becoming increasingly popular as a source of renewable energy. One key factor that significantly affects the performance of RPV systems is the tilt angle of the solar panels. This study aims to determine the optimal tilt angle to maximize electricity production for the RPV system installed on academic building, Department of Electrical Engineering, Faculty of Engineering, University of Riau. The research method used is the PVSyst simulation. The simulation data input was used as daily weather for one year. In this study, variations in roof tilt angles of 5°, 10°, 15°, 20°, and 25° were examined. The results show that the optimal tilt angles for this location are 5° and 10°. At a 5° tilt angle, the RPV can generate 247,128 kWh per year with a performance ratio (PR) of 83%. And then at a 10° tilt angle, the system can generate 248,012 kWh per year with a PR of 82%. Based on the simulation results, other tilt angles also produced higher energy outputs but yielded lower PR values. This study provides practical recommendations for designing RPV systems in regions with similar weather conditions.